Estudo da redução do óxido de grafeno assistido por laser para aplicações em eletrônica flexível - Bonando, Matheus Guitti (2020)
Advances in printing technologies have transformed the field of electronics and sensors. The implementation of new materials and the constant development of standardization techniques, flexible electronic devices, and easy to produce have proved to be increasingly viable, being an alternative with more prominence and research. Thus, it is possible to replace rigid silicon electronics with new flexible integrated circuits that require low production costs and high reliability. Carbon-based materials have proved to be the most promising in this regard; among them is graphene, the first 2D material to be isolated from a graphite sample. The material has attracted researchers' attention for its excellent thermal, mechanical, optical, and electrical properties. As it is a monatomic thick material, its difficulty in handling, transferring, and manufacturing on a large scale are still challenging. Based on this, its graphene oxide derivative (GO) can be manufactured on a large scale, adhering to different materials and surfaces, and manipulated with ease and flexibility without affecting its physical properties. The reduction process can subsequently occur chemically, thermally, or by photoreduction to obtain reduced graphene oxide (rGO), which has structures and properties like those of graphene, allowing the creation of conductive patterns on different substrates. This work presents the fabrication of flexible conductive patterns of rGO by laser on a nitrocellulose membrane. The thin films of GO were manufactured through a vacuum filtration system where the best results are obtained using a volume of 3 mL and a concentration of 1 mg/mL on a nitrocellulose membrane with 0.2 µm pores as a substrate. The conductive patterns of rGO were made by two CW laser (λ = 488 and 532 nm) with a power of 20 mW, and a pulsed laser (λ = 405 nm), a frequency of 20 kHz and an optical power of 3 mW. In the laser reduction of graphene oxide, there is no need to use any chemical product, which contributes to green chemistry, that is, positively affecting the environment and can be transferred to other substrates. The minimum sheet resistance obtained from reduced graphene oxide with laser was 162.5 ± 18.7 Ω/sq.